The Effect of Green Accounting And Environmental Performance on Financial Performance - Nursari, Ayu; Azzahra, Safira; Musyafa'ah, Siti (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of green accounting and environmental performance on the financial performance of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. This study uses a descriptive quantitative approach with secondary data from the company's annual and sustainability reports. Green accounting is measured by the ratio of CSR expenditure to net profit, environmental performance using the PROPER score, and financial performance is measured by the Return on Assets (ROA) ratio. The results of multiple linear regression analysis showed that green accounting had a positive and significant influence on financial performance, while environmental performance had no significant influence. The limitations of this study lie in the limited scope of sectors and time and have not considered other relevant variables. This research contributes to the ongoing accounting literature by highlighting the importance of green accounting disclosure as a strategy to improve financial performance and company reputation. The novelty of this study lies in the financial approach in the measurement of green accounting and the evaluation of the effectiveness of the PROPER score in explaining the financial performance of the company.